ESL STUDENTS' INTERPRETATIONS OF PUN IN ENGLISH JOKES - Pasaribu, Tiara Kristina; Pasaribu, Donna Ria; Simanjuntak, Hotnida Irawaty; Hia, Leli Arlinawati; Halawa, Ardiwan (TELL - US JOURNAL, 2025)
This research is expected to broaden students' perspectives through humor, specifically "puns" or "one-liners." The interpretation of ESL students towards English jokes will be analyzed to understand their comprehension of "wordplay." The objectives of the study are to determine how ESL students interpret puns and to identify the difficulties arising from misinterpretations of puns. This study employs a qualitative descriptive approach. Questionnaires and interviews are used to help understand linguistic difficulties and cultural knowledge, exploring students' cultural understanding by exposing them to the use of wordplay in English.The novelty of this research lies in analyzing puns from the perspective of ESL students in North Sumatra, comprising Batak and Nias ethnic students. The findings indicate that students' interpretations of puns show that most can understand the humor if their vocabulary is strong. They can interpret homonyms effectively. Cultural knowledge plays a crucial role; the broader their experiences in the outside world, the better they can appreciate pun humor. Good metacognitive skills also aid students in interpreting pun humor, evident in how they attempt to understand wordplay. Some students can "understand" the jokes due to their familiarity with the words through prior experiences.The researcher hopes that students' vocabulary can be enhanced so they grasp double meanings in humor better. Students are encouraged to expand their cultural knowledge and metacognitive skills by exposing themselves more to foreign cultures through reading, listening to news, social media, or new experiences.